Mapania sapuaniana (Cyperaceae), a new sedge species from Sarawak - Zinnirah, Shabdin; Culham, Alastair; Simpson, David A.; Meeklong, K (National Herbarium Nederland, 2013)
Mapania sapuaniana, a spectacular new sedge species from Lanjak Entimau, Sarawak, is described and illustrated. It is closely related to M. richardsii and M. borneensis but differs in having broad leaves with a distinct pseudopetiole, reddish purple or maroon coloration on the underside of the leaf and petiole and an inflorescence composed of several spikes.